Simple and Efficient 1, 3‐Isomerization of Allylic Alcohols using a Supported Monomeric Vanadium‐Oxide Catalyst. Issue 10 (14th June 2013) - Mitsudome, Takato; Sueoka, Shoichiro; Ikeda, Satoshi; Mizugaki, Tomoo; Jitsukawa, Koichiro; Kaneda, Kiyotomi
<x xml:space="preserve">Abstract</x> Promotion by group high five: Silica‐supported monomeric vanadium‐oxide promoted the isomerization of various allylic alcohols, including under scaled‐up and solvent‐free reaction conditions. This catalyst also exhibited high reusability with no drop in activity.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>